Associations of Sustainable Development Goals Accelerators With Adolescents' Well-Being According to Head-of-Household's Disability Status-A Cross-Sectional Study From Zambia - David Chipanta; David Chipanta; Janne Estill; Heidi Stöckl; Lucas Hertzog; Elona Toska; Elona Toska; Elona Toska; Patrick Chanda; Jason Mwanza; Kelly Kaila; Chisangu Matome; et al. (Frontiers Media S.A., 2022)
Objectives: We examined associations between accelerators (interventions impacting ≥2 SDG targets) and SDG-aligned well-being indicators among adolescents 16-24 years old in Zambia.Methods: We surveyed adults from 1,800 randomly sampled households receiving social cash transfers. We examined associations between accelerators (social cash transfers, life-long learning, mobile phone access) and seven well-being indicators among adolescents using multivariate logistic regressions.Results: The sample comprised 1,725 adolescents, 881 (51.1%) girls. Mobile phone access was associated with no poverty (adjusted Odds Ratio [aOR] 2.08, p < 0.001), informal cash transfers (aOR 1.82, p = 0.004), and seeking mental health support (aOR 1.61, p = 0.020). Social cash transfers were associated with no disability-related health restrictions (aOR 2.56, p = 0.004) and lesser odds of seeking mental health support (aOR 0.53, p = 0.029). Life-long learning was associated with informal cash transfers (aOR 3.49, p < 0.001) and lower school enrollment (aOR 0.70, p = 0.004). Adolescents with disabled head-of-household reported worse poverty, good health but less suicidal ideation.Conclusions: Social cash transfers, life-long learning, and mobile phone access were positively associated with well-being indicators. Adolescents living with disabled head-of-household benefited less. Governments should implement policies to correct disability-related inequalities.